John Jaffray:Victorian Bookbinder, Chartist and Trade Unionist. (2014) - Bookbinder, Victorian; Fig, Unionist P. J. M. Marks; Jaffray, John; Jeffray, John Jaffray John Jeffery John; Jaffray, John; Jaffray, John; Jaffray, Joseph; Howe, Ellic
No abstract available